A fully inkjet-printed disposable glucose sensor on paper - Eloïse Bihar (Nature Portfolio, 2018)
Glucose in saliva tested by paper sensors Saliva based glucose test can now be made easily and cheaply with inkjet-printed paper sensors enabled by enzyme glucose oxidase. Most present technologies rely on blood tests to monitor glucose concentration. To tackle this problem, a collaborative international team led by Prof Sahika Inal from King Abdullah University of Science and Technology, Saudi Arabia designs disposable glucose sensors based on saliva testing. They construct the analytical device by ink-jet printing cheap conducting polymer, an enzyme containing biological film and an encapsulation layer on paper substrates to measure glucose concentrations in human saliva. The devices stay active for more than a month in air-free storage conditions with minor performance losses. The high versatility and adaptability of the material system enable the possibilities to design affordable and expandable enzyme testing based diagnostic platforms.